2009
DOI: 10.1242/jeb.030858
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and behavioral plasticity of pheromone response and its hormonal control in a long-lived moth

Abstract: SUMMARYReproductive success in many animals depends on the efficient production of and response to sexual signals. In insects, plasticity in sexual communication is predicted in species that experience periods of reproductive inactivity when environmental conditions are unsuitable for reproduction. Here, we study a long-lived moth Caloptilia fraxinella (Ely) (Lepidoptera: Gracillariidae) that is reproductively inactive from eclosion in summer until the following spring. Male sex pheromone responsiveness is pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 41 publications
2
30
2
Order By: Relevance
“…In the present work, we show that the saturated lactone analog (hereafter called analog), dodecan-12-olide, also has biological activity in terms of electrophysiological and olfactometer responses and trapping efficacy, indicating not only function but also plasticity in pheromone structure, perception, and response (Lemmen and Evenden 2009). …”
Section: Introductionmentioning
confidence: 61%
“…In the present work, we show that the saturated lactone analog (hereafter called analog), dodecan-12-olide, also has biological activity in terms of electrophysiological and olfactometer responses and trapping efficacy, indicating not only function but also plasticity in pheromone structure, perception, and response (Lemmen and Evenden 2009). …”
Section: Introductionmentioning
confidence: 61%
“…JH influences the age-dependent behavioral and central nervous responses to sex pheromone in the moth, Agrotis ipsilon [13], [14]. JH also modulates behavioral and peripheral pheromone responses in the long-lived moth Caloptilia fraxinella [9]. The role of 20 E in the control of sex pheromone responses is less studied.…”
Section: Introductionmentioning
confidence: 99%
“…Among its important roles, JH can influence mating itself, in some insect species, through regulation of sex pheromone biosynthesis (Lemmen and Evenden, 2009). However, Bober et al (2010) recently reported that JH does not influence the expression of the gene encoding the pheromone biosynthesis activating neuropeptide receptor (PBAN-R) in the moth Helicoverpa armigera.…”
mentioning
confidence: 99%